BETWEEN STRATEGY AND PRACTICE: LEADERSHIP AND THE CONSTRUCTION OF ORGANIZATIONAL GROWTH IN BUSINESS CONTEXTS - Caetano, Plinio Alexandre dos Santos; Paiva, Ana Flávia Faria; Nascimento, Graziele Martins Fraga (Seven Editora, 2026)
Leadership has become a central dimension in understanding strategic implementation processes within organizations operating in environments marked by competitiveness, constant change, and the ongoing need for adaptation. This chapter examines how business leaders from medium- and large-sized companies perceive their role in conducting organizational growth strategies, considering the articulation between people, processes, and results. The study adopted a mixed-methods approach and was developed through a survey based on a structured questionnaire applied to 16 leaders holding strategic positions across different organizational sectors. The findings indicate that leadership is recognized as a structuring element of strategic execution, particularly regarding clarity in goal definition, encouragement of collaboration, and systematic monitoring of organizational performance. Participants’ narratives further reveal that leaders perceive themselves as mediators between planning and practice, responsible for aligning teams, fostering autonomy, and sustaining adaptation processes. It is concluded that leadership performs an integrative role in organizational growth processes, contributing to strategic effectiveness in complex organizational contexts.